Linguistic Variation and Change in Online Communities: (Lexical Innovation and Syntactic Structures among Saudi Participants) - Nada Alshehri (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
This study explores linguistic variation and innovation in Saudi online communities, analyzing 100 posts and 300 comments from platforms such as Twitter, Instagram, and forums. The study used both qualitative (analysis of specific language use patterns) and quantitative (descriptive statistics and regression analysis) approaches. The results reveal significant trends in lexical innovation and syntactic simplifications, with 40% of posts showing evidence of syntactic deviations and 25% incorporating English borrowings, particularly in discussions related to technology and entertainment. Regression analysis indicates that gender is a significant factor in linguistic innovation, with female users more likely to adopt new linguistic forms than male users (p < 0.01). The study also demonstrates that online communities provide a fertile ground for linguistic change, offering spaces where users can experiment with new forms of communication. These findings align with previous studies on language change in online environments while contributing new insights into the specific dynamics of Saudi digital communication. The study highlights the growing role of digital platforms in shaping language practices, particularly in multilingual and code-switching contexts. The implications of this research are significant for understanding how online spaces are reshaping linguistic norms in Saudi Arabia, offering a dynamic site for language evolution.